A new Mental Health Act for Malta. Issue 3 (August 2014) - Zahra, Anthony; Camilleri, Miriam; Cachia, John
Abstract : Until recently, the care of persons with mental disorder in Malta was regulated by mental health legislation enacted in 1976. This was closely modelled on the 1959 British Mental Health Act. Now, the Mental Health Act 2012 is being implemented in two steps, in 2013 and 2014. The paper reviews its provisions.